Physical and chemical properties of CuCr2O4-based glass fiber catalyst synthesized by surface thermo-synthesis method - Elyshev A.; Larina T.; Cherepanova S.; Mikenin P.; Lopatin S.; Zazhigalov S.; Pisarev D.; Baranov D.; Zagoruiko A. N. Andrey Nikolaevich (2016, 2016)
Title screen